2021
DOI: 10.1182/blood-2021-150280
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD37 Alpha-Amanitin Conjugated Antibodies As Therapeutic Weapons for Richter's Syndrome

Abstract: The leukocyte surface antigen CD37 (TSPAN26), a member of the tetraspanin superfamily, is widely expressed on most malignant B cells, making it an actionable target for treatment of patients with chronic lymphocytic leukemia (CLL) and other B-cell non-Hodgkin lymphoma (NHL) indications. Accordingly, αCD37 antibodies have shown promising results in phase 1/2 clinical trials for CLL and NHL. Richter's syndrome (RS) is the transformation of CLL into an aggressive and rapidly fatal lymphoma, typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Overall, our study adds new knowledge to the current state of the art on the regulation of CD37, which in light of recent findings 11 , 12 , 18 , 26 , 31 , 32 constitutes an attractive therapeutic target for immunotherapies. The results of our study once again prove that CD37 is highly variable in DLBCL patients.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Overall, our study adds new knowledge to the current state of the art on the regulation of CD37, which in light of recent findings 11 , 12 , 18 , 26 , 31 , 32 constitutes an attractive therapeutic target for immunotherapies. The results of our study once again prove that CD37 is highly variable in DLBCL patients.…”
Section: Discussionsupporting
confidence: 64%
“… 26 , 31 On the other hand, using ADCs based on the preclinically explored ADC – naratuximab emtansine we show that CD20 loss facilitates CD37 endocytosis and it may translate to increased efficacy of anti-CD37 ADCs that have recently been presented as a highly efficient strategy in B-cell malignancies in vitro and in murine models. 32 The efficacy of ADCs relies on the endocytosis of the target antigen-ADC complex and the release of the cytotoxic payload to the cytoplasm. It has already been reported that rituximab synergizes with naratuximab emtansine by increasing the endocytosis of CD37.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, our study adds new knowledge on the current state of the art on the regulation of CD37, which in the light of the recent findings (11,12,18,24,29,30) constitutes an attractive therapeutic target for immunotherapies. The results of our study once again prove that CD37 is highly variable in DLBCL patients.…”
Section: Discussionsupporting
confidence: 54%
“…On the other hand, we hypothesize that CD20 loss facilitates CD37 endocytosis and it may translate to increased efficacy of anti-CD37 ADCs that have recently been presented as a highly efficient strategy in B-cell malignancies in vitro and in murine models (30). The efficacy of ADCs relies on the endocytosis of the target antigen-ADC complex and the release of the cytotoxic payload to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of RS cells with these compounds, both ex vivo and in vivo, induced apoptosis and significantly prolonged survival of treated mice, after a single-dose administration of these ADCs, making CD37 an interesting target for RS patients (Fig. 1A) [59].…”
Section: Drug-conjugated Antibodiesmentioning
confidence: 99%